Pengetahuan kepala rumah tangga tentang Third-Hand Smoke (THS) dan keluhan pernapasan pada anak - Gst. Kade Adi Widyas Pranata; Anak Agung Istri Wulan Krisnandari Dalem (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Householder knowledge regarding third-hand tobacco smoke exposure and respiratory complaints in children Background: Third-hand smoke (THS) is very dangerous, especially for children because of its content, properties, and the ability to last a long time on the surface of objects for months. Parents or families do not seem to care and know this hidden danger since they think as long as they do not smoke in front of their children, it means there is no problem.Purpose: To identify the householder knowledge regarding third-hand tobacco smoke exposure and respiratory complaints in childrenMethod: This descriptive survey research with a cross-sectional approach was carried from August to November 2020 with householders of active smokers. The sampling technique was cluster sampling with a sample size of 561 respondents. The research instrument used the